Radio-frequency magnetron sputtering deposition process for In2O3:H transparent conductive oxide films for application in Cu(In,Ga)Se2 solar cells - Alves, Marina (2023)
Typical Cu(In,Ga)Se2 solar cells are deposited on an opaque molybdenum back contact. However, for applications such as bifacial, semi-transparent or tandem solar cells a transparent back contact is required, for which various transparent conductive oxides have been tested, such as indium- or fluorine-doped tin oxide, and hydrogen-doped indium oxide. Here, a radio-frequency magnetron sputtering deposition process for In2O3:H (IOH) is investigated, where H is supplied from a Ar/H2 (5%) mixed gas and oxygen is pulsed during the entire deposition at room temperature. After deposition, the films are post-annealed in vacuum to optimize their optoelectronic properties. The oxygen plays an important role for the optoelectronic properties, where a high content of oxygen allows higher transparency but also increases the film sheet resistance. Optimum oxygen and Ar/H2 partial pressures of 3.2 E-2 Pa and 13E-2 Pa, respectively, were found, producing IOH films with average visible transparency of 87% and sheet resistance after annealing of 19 Ohm/sq.